Emotions, communicational process and inclusion of people with disabilities in the work context - Nogueira, Marta (2022)
The general objective of this research focuses on understanding how the labor market integrates people with disabilities (PwD), understanding their emotions and how they manage them throughout the work day, and knowing how communication is processed in theworkplace. The following specific objectives were then defined: to know the degree of awareness that disabled workers have about their emotions in their daily interactions in the workplace,and to analyze the communicative interactions of PwD in the work environment. A mixed methodology was chosen, using qualitative and quantitative research. The qualitative methodology used semi-structured interviews, and the quantitative methodology used a questionnaire. The sample was made up of 50 disabled workers and314 co-workers of the same (n=314), employees of the Auchan Portugal Group. The results showed that: of the four dimensions under study (General Perception of Hiring, Emotional Intelligence, Interpersonal Communicationand Integration/Insertion in the workplace) the great majority of PwD co-workers agreedor totally agreed with the items of the four dimensions, which suggests apositive score with the themes under study, the PwDare able to identify the emotions that most characterize the day-to-day at work, but most disguise the discomfort felt and do not clearly communicate to the other what emotion they felt, most PwDcommunicate to the other the behavior that caused them discomfort, PwDdo not consider the communication channels confusing, most PwDfeel integrated in the company and state that no specific adaptation has been made,most of the interviewees suggest a greater sensitivity on the part of the employer and work adapted to the person and his/her disability.